Morphological and genetic characterization of an emerging Azorean horse breed: the Terceira Pony - Lopes, Maria S.; Mendonça, Duarte; Rojer, Horst; Cabral, Verónica; Bettencourt, Sílvia X.; da Câmara Machado, Artur (Frontiers in Genetics, 2015)
The Terceira Pony is a horse indigenous to Terceira Island in the Azores. These horses were very important during the colonization of the island and due to their very balanced proportions and correct gaits, with an average withers height of 1.28 m, the Terceira Pony is often confused with a miniature pure-bred Lusitano. This population was officially recognized as the fourth Portuguese equine breed by the national authorities in January 2014. The aim of this study was to analyze the morphology and the genetic diversity by means of microsatellite markers of this emerging horse breed. The biometric data consisted of 28 body measurements and 9 angles from 30 animals (11 sires, 19 dams). As the Terceira pony is now a recognized horse breed and gains popularity, primarily by breeders and the younger riding classes, the obtained information will be very useful for conservation and management purposes on maximizing its genetic diversity and solidifying the desirable phenotypic traits.